Identification of Class 1 Integron of Escherichia coli from Street Foods in Jakarta - . FRISCA; BIBIANA WIDYATI LAY; DIANA ELIZABETH WATURANGI (Microbiology Indonesia, 2007)
A total of 43 Escherichia coli isolates were identified from school street foods located in Northern and Southern Jakarta. The isolates were examined for antibiotic resistance using five antibiotics discs (ampicillin, kanamycin, streptomycin, trimethoprim, tetracycline) and screened for the class 1 integron with specific conserved region primer using PCR amplification. The antibiotic diffusion test revealed three isolates (7%) with resistance to multiple antibiotics. PCR detection of integron regions showed one isolate possessed a class 1 integron bearing one gene cassette with ~700bp amplicon size. DNA sequencing showed that the gene cassette was resistant to trimethoprim determinant type V (dhfrV). The integron bearing E. coli strain could become a threat for the widespread distribution of an antibiotic resistance gene especially for pathogenic bacteria.